2015
DOI: 10.1128/jvi.02382-14
|View full text |Cite|
|
Sign up to set email alerts
|

Shift in Monocyte Apoptosis with Increasing Viral Load and Change in Apoptosis-Related ISG/Bcl2 Family Gene Expression in Chronically HIV-1-Infected Subjects

Abstract: Although monocytes and macrophages are targets of HIV-1-mediated immunopathology, the impact of high viremia on activation-induced monocyte apoptosis relative to monocyte and macrophage activation changes remains undetermined. In this study, we determined constitutive and oxidative stress-induced monocyte apoptosis in uninfected and HIV ؉ individuals across a spectrum of viral loads (n ‫؍‬ 35; range, 2,243 to 1,355,998 HIV-1 RNA copies/ml) and CD4 counts (range, 26 to 801 cells/mm 3 ). Both constitutive apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 75 publications
3
15
0
Order By: Relevance
“…In addition, plasma CXCL13 could also be considered since it has been reported to correlate with the level of plasma viral load in HIV-infected cohorts (42), although our study indicated that not all SIV-infected macaques with high viral load exhibited high monocyte turnover, so this is another area of exploration. Patro et al (43) reported that apoptosis of monocytes correlated with HIV plasma levels and while SIV levels did not necessarily correlate with disease progression in our studies using rhesus macaques, monocyte apoptosis could also be considered for its relationship or impact on monocyte turnover. The nonhuman primate model of AIDS is especially amenable to examining these mechanisms and their impact on both populations of lung macrophages via BAL and tissue biopsy and thus provides an important resource for studies about the mechanisms of HIV/AIDS and HANA pathogenesis as well as for defining sites of viral reservoirs necessary to rationally target effective therapies.…”
Section: Discussionmentioning
confidence: 59%
“…In addition, plasma CXCL13 could also be considered since it has been reported to correlate with the level of plasma viral load in HIV-infected cohorts (42), although our study indicated that not all SIV-infected macaques with high viral load exhibited high monocyte turnover, so this is another area of exploration. Patro et al (43) reported that apoptosis of monocytes correlated with HIV plasma levels and while SIV levels did not necessarily correlate with disease progression in our studies using rhesus macaques, monocyte apoptosis could also be considered for its relationship or impact on monocyte turnover. The nonhuman primate model of AIDS is especially amenable to examining these mechanisms and their impact on both populations of lung macrophages via BAL and tissue biopsy and thus provides an important resource for studies about the mechanisms of HIV/AIDS and HANA pathogenesis as well as for defining sites of viral reservoirs necessary to rationally target effective therapies.…”
Section: Discussionmentioning
confidence: 59%
“…HIV results in a shift from “classical” CD14++CD16− to “non-classical” CD14+CD16+ and “intermediate” CD14++CD16+ monocytes, which are associated with an inflammatory phenotype [4042] and greater viremia and/or CD4+ T cell depletion [42, 43]. High expression of the PD1 homologue (PD-1H), which is associated with increased production of TNF, IL-1β, and IL-6, may also contribute to the pro-inflammatory state of these monocytes [44].…”
Section: Specific Immunologic Pathways That Predict Disease In Hiv Inmentioning
confidence: 99%
“…High plasma IP-10, IL-6 and sCD14 all consistently predict increased subsequent morbidity and mortality during ART [42, 43, 60], and high sCD163 levels have been associated with surrogate markers of neurologic and cardiovascular disease (though perhaps not cardiovascular events [61]), as well as all-cause mortality in a recent report [26, 5759, 62, 63]. As many of these biomarkers of monocyte activation may be increased by smoking and/or alcohol use, many of these associations with morbidity and mortality may be at least in part driven by behavioral risk factors and not HIV itself, though a recent report suggests that these associations persist despite adjustment for behavioral risk factors [64].…”
Section: Specific Immunologic Pathways That Predict Disease In Hiv Inmentioning
confidence: 99%
“…36,37 Family members of BCL can help B cells in patients with HIV/AIDS evade elimination by Fas-mediated cell death. 38,39 In addition, NFKBIA (NF-κB inhibitor α) encodes a protein that blocks NF-κB. 40 After TCM intervention, BCL2A1, NFKBIA, and PTGS2 tended to normalize.…”
Section: Discussionmentioning
confidence: 99%